2007
DOI: 10.1007/s00401-006-0176-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GAD67 mRNA levels in cerebellar Purkinje cells in autism: pathophysiological implications

Abstract: The recent identification of decreased protein levels of glutamate decarboxylase (GAD) 65 and 67 isoforms in the autistic cerebellar tissue raises the possibility that abnormal regulation of GABA production in individual neurons may contribute to the clinical features of autism. Reductions in Purkinje cell number have been widely reported in autism. It is not known whether the GAD changes also occur in Purkinje cells at the level of transcription. Using a novel approach, the present study quantified GAD67 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
154
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(180 citation statements)
references
References 78 publications
21
154
1
2
Order By: Relevance
“…2). Decreases in ν or c may reflect decreases in GABArelated inhibition that are also consistent with physiological data on autism (7,23,31,32). Changes in the extent of neuronal pooling in the suppressive field SðX, θÞ (e.g., altered lateral connectivity) could also alter the amount of inhibition acting on a neuron.…”
Section: Connecting Divisive Normalization and Autismsupporting
confidence: 69%
See 2 more Smart Citations
“…2). Decreases in ν or c may reflect decreases in GABArelated inhibition that are also consistent with physiological data on autism (7,23,31,32). Changes in the extent of neuronal pooling in the suppressive field SðX, θÞ (e.g., altered lateral connectivity) could also alter the amount of inhibition acting on a neuron.…”
Section: Connecting Divisive Normalization and Autismsupporting
confidence: 69%
“…5D). Supporting this idea, the GABAergic pathways likely contribute to autism (7,8,31,32), and GABA A and GABA B can contribute differently to divisive normalization. In V1, GABA A modulates response gain but not contrast sensitivity (77), suggesting it contributes to the suppressive field gain term (c) but not the semisaturation constant (ν).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Glutamic acid decarboxylase (GAD) is an enzyme responsible for catalysing the decarboxylation of glutamic acid to form GABA and exists in two isoforms: 65 and 67 (GAD65; GAD67). Post mortem studies have revealed that both GAD65 and GAD 67 are decreased in the cerebellum and parietal cortex of individuals with ASD (Fatemi et al, 2002;Yip, glutamate-glutamine cycle are decreased in post mortem brain tissue of individuals with ASD, thus also suggesting a dysfunction in excitatory neurotransmission in ASD.…”
Section: Cellular Abnormalitiesmentioning
confidence: 99%
“…Differences in the expression of GAD isoforms have been reported in people with ASD: GAD65 and GAD67 has been reported to be lower in parietal and cerebellar cortices [39]; GAD67 mRNA levels have been observed as lower in cerebellar Purkinje cells; GAD65 mRNA is lower in select subpopulations of neurons in the cerebellar dentate nuclei [76,77]; and GAD67 mRNA expression is greater in cerebellar interneurons [78]. In the current study, animals exposed had lower GAD65 in all 6 brain regions examined; GAD67 was lower in MB, OB and PFC, but increased in CB, HP and STR.…”
Section: Gad Alteration In Asdmentioning
confidence: 99%